The Impact of Pasteurization on Tetracycline Residues, Physicochemical, Microbiological, and Antioxidant Properties of Acacia Honey (Menara Perkebunan, 2026)
Honey is recognized for its high nutritional and functional value, yet it remains vulnerable to contamination by antibiotic residues such as tetracycline when beekeeping practices are not properly managed. Post-harvest pasteurization is widely utilized to improve honey safety and quality. This study examined the effects of pasteurizing honey at 60°C for 10, 20, or 30 minutes on tetracycline and oxytetracycline residue levels, as well as on the physicochemical, microbiological, and antioxidant properties of acacia honey (Apis mellifera). Honey samples were artificially contaminated with antibiotics at 1 µg/g and analyzed using high-performance liquid chromatography (HPLC). Pasteurization at 60°C reduced oxytetracycline residues by approximately 33% (P
Keywords: antibiotic degradation; diastase enzyme; flavonoids; hydroxymethyl-furfural; reducing sugar